Epichloë Endophyte Alters Bacterial Nitrogen-Cycling Gene Abundance in the Rhizosphere Soil of Perennial Ryegrass - Munire Maimaitiyiming; Yanxiang Huang; Letian Jia; Mofan Wu; Zhenjiang Chen (Biology, 2025)
Perennial ryegrass (Lolium perenne), an important forage and turfgrass species, can establish a mutualistic symbiosis with the fungal endophyte Epichloë festucae var. lolii. Although the physiological and ecological impacts of endophyte infection on ryegrass have been extensively investigated, the response of the soil microbial community and nitrogen-cycling gene to this relationship has received much less attention. The present study emphasized abundance and diversity variation in the AOB-amoA, nirK and nosZ functional genes in the rhizosphere soil of the endophyte–ryegrass symbiosis following litter addition. We sampled four times: at T0 (prior to first litter addition), T1 (post 120 d of 1st litter addition), T2 (post 120 d of 2nd litter addition) and T3 (post 120 d of 3rd litter addition) times. Real-time fluorescence quantitative PCR (qPCR) and PCR amplification and sequencing were used to characterize the abundance and diversity of the AOB-amoA, nirK and nosZ genes in rhizosphere soils of endophyte-infected (E+) plants and endophyte-free (E−) plants. A significant enhancement of total Phosphorus (P), Soil Organic Carbon (SOC), Ammonium ion (NH4+) and Nitrate ion (NO3−) contents in the rhizosphere soil was recorded in endophyte-infected plants at different sampling times compared to endophyte-free plants (p ≤ 0.05). The absolute abundance of the AOB-amoA gene at T0 and T1 times was higher, as was the absolute abundance of the nosZ gene at T0, T1 and T3 times in the E+ plant rhizophere soils relative to E− plant rhizosphere soils. A significant change in relative abundance of the AOB-amoA and nosZ genes in the host rhizophere soils of endophyte-infected plants at T1 and T3 times was observed. The experiment failed to show any significant alteration in abundance and diversity of the nirK gene, and diversity of the AOB-amoA and nosZ genes. Analysis of the abundance and diversity of the nirK gene indicated that changes in soil properties accounted for approximately 70.38% of the variation along the first axis and 16.69% along the second axis, and soil NH4+ (p = 0.002, 50.4%) and soil C/P ratio (p = 0.012, 15.8%) had a strong effect. The changes in community abundance and diversity of the AOB-amoA and nosZ genes were mainly related to soil pH, N/P ratio and NH4+ content. The results demonstrate that the existence of tripartite interactions among the foliar endophyte E. festucae var. Lolii, L. perenne and soil nitrogen-cycling gene has important implications for reducing soil losses on N.